I don't understand how my calc book worked this out to convert to the a/(1-r) form: $\displaystyle \frac {1}{2x-5} = \frac{-1}{11-2(x+3)}$
Follow Math Help Forum on Facebook and Google+
Originally Posted by saiyanmx89 I don't understand how my calc book worked this out to convert to the a/(1-r) form: $\displaystyle \frac {1}{2x-5} = \frac{-1}{11-2(x+3)}$ this is a weird form to bring it to, i guess this was a follow up question? anyway: $\displaystyle \frac 1{2x - 5} = \frac {-1}{5 - 2x} = \frac {-1}{11 - 6 - 2x} = \frac {-1}{11 - 2(x + 3)}$
View Tag Cloud